Estimation of surface moisture using soil wetness index based on : LST and NDVI / Raja Amirah Raja Razlan - Raja Razlan, Raja Amirah (2018)
Surface soil wetness determines moisture availability that controls the response and feedback mechanisms between land surface and atmospheric processes. The purpose of this research is to estimate the soil moisture at Kuala Krai. The estimation of surface soil moisture is important for the agricultural safety. Soil wetness index has been used to estimate the soil moisture for this study. Therefore, mathematical model has been used to calculate the soil wetness index. Moreover, this research has used Normalized Differential Vegetation Index (NDVI) and Land Surface Temperature (LST) as the parameters to calculate soil wetness index. Results of this study have showed three types of maps which is land surface temperature, NDVI and soil wetness index maps. Other than that, the scatter plot to show relationship between the results have been done. In conclusion, this study will give beneficial to the agricultural activities to determine the good condition of soil for plantation.